The Role of Kuwait University libraries in supporting graduate students’ research - Motawah, Wafaa Al; Sen, Barbara; Willett, Peter (Qualitative and Quantitative Methods in Libraries, 2019)
This paper reports a survey that was conducted at Kuwait University to explore postgraduate taught-course students’ perceptions of the resources and services provided to support the research components of their degrees and to highlight their use of their particular college library for that research. A questionnaire was developed containing 29 closed and 2 open questions and responses were obtained from 578 students studying in four colleges (arts, engineering, law, and science). Whilst the students provided generally positive responses to the survey, analyses with SPSS and NVivo showed marked differences between the four subject groups, with the limitations that were identified providing vital information for improving library services to meet the graduate students’ information needs.